Uji In-Vitro Kandungan Sun Protection Factor (Spf) Ekstrak Etanol Kulit Pisang Nangka (Musa Paradisiaca L.) Dengan Metode Spektrofotometri Uv-Vis - Tantriska Wijanti; Eva Pahlani; Saniyah Nur Hasanah (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2025)
Ultraviolet (UV) radiation consists of UV-A, UV-B, and UV-C rays. Exposure to UV radiation can cause skin damage, thereby necessitating protection in the form of sunscreen. The peel of jackfruit banana (Musa paradisiaca L.) has potential as a natural sunscreen agent due to its content of secondary metabolites such as alkaloids, flavonoids, tannins, and polyphenols. This quantitative study aims to determine the Sun Protection Factor (SPF) value of the ethanol extract of jackfruit banana peel. The extraction process was carried out using maceration and remaceration methods with 70% ethanol. The SPF value was tested in vitro using the Mansur method with UV-Vis spectrophotometry at wavelengths of 290–320 nm with 5 nm intervals. The results showed that the macerated extract at a concentration of 2000 ppm had an average SPF value of 7.762, categorized as providing extra protection. Meanwhile, the remacerated extract showed an average SPF value of 3.102, categorized as providing minimal protection. It can be concluded that the macerated extract has a higher effectiveness in protecting against UV radiation.